Evaluating on Time Performance of Urban Bus Services in Southern States of Peninsular of Malaysia - Bakar M.F.A.; Norhisham S.; Azman T.N.A.T.N.; Saad N.M.; Azlan N.N.I.M.; Shkuri N.S.M.; Yukawa S.; Syamsir A. (Springer Science and Business Media Deutschland GmbH, 2023)
Bus transportation; Buses; Bus services; Continuous development; Malaysia; On-time performance; Quality-of-service; Rapid urbanizations; Southern state; Urban areas; Urban bus; Urban bus service; Quality of service